Inovasi Kemandirian Keluarga untuk Mendukung Ketahanan Pangan: Pakan Ternak Ayam - Wiliyanti, Vandan; Al-Rafi, M.; Fitriyana, Almaratul; Anggraini, Elen Dea; Ramadania, Faisya; Nurohman, Idhar; Jamiatun, Jamiatun; Fatimah, Julita Ripma; Taufiqqurahman, Moh Adek; Kimlie, Sesilia Wulan (Civiliza Publishing, 2024)
Food security an important issue like affects the quality of human resources and social stability of a country. As an archipelagic country that depends on the agriculture, plantation, fisheries, and livestock sectors, Indonesia still faces challenges in meeting the food needs of animal protein sources, especially from chickens. Although purebred chicken production dominates, its dependence on imports makes it vulnerable. Meanwhile, free-range chickens have great potential, but are limited by low productivity and high mortality rates. This research aims to develop innovations in the maintenance of free-range chickens to support family food security. method used is Participatory Action Research (PAR), involves the initial mapping stages, determining action solutions, and implementing actions. The main activities are seminars and socialization with the theme